Cause of Emergency Department Mortality; a Case-control Study - Alimohammadi, Hossein; Bidarizerehpoosh, Farahnaz; Mirmohammadi, Farzaneh; Shahrami, Ali; Heidari, Kamran; Sabzghabaie, Anita; Keikha, Shahram (Archives of Academic Emergency Medicine, 2018)
Introduction: Based on previous studies, cardiovascular diseases, traffic accidents, traumas and cancers are the most important etiology of mortalities in emergency departments (ED). However, contradictory findings have been reported in relation to mortality in emergency departments. Therefore, the present study was undertaken to evaluate the role of clinical factors in mortality among patients referring to an emergency department in a third-level hospital in Tehran, Iran. Methods: In the present case-control study, all the patients over 18 years of age were evaluated, referring to the ED of Imam Hossein Hospital, Tehran, Iran, from the beginning of 2009 to the end of 2010. The patients died in the ED were placed in the case group and those discharged or hospitalized in other hospital wards in the control group. Demographic data, background diseases, and the final diagnoses were recorded. Chi-squared test, multivariate logistic regression, and Pearson’s correlation coefficient were used to evaluate the relationship between the variables mentioned above and patient mortality. Results: 2907 patients (969 (59.9% male) in the case and 1938 (62.2% male) in the control groups) were evaluated. Cardiovascular diseases (39.2%), severe traumas (18.5%), and cerebrovascular accidents (17.7%) were the most frequent etiology of patient mortality in ED. Multivariate regression analysis showed that presentation with cardiovascular complaints (OR=7.3; 95% CI: 3.5-16.1; p<0.001), a history of hypertension (OR=5.4; 95% CI: 1.2-12.3; p<0.001), severe trauma (OR=4.6; 95% CI: 2.0-13.2; p<0.001), age over 60 (OR=3.8; 95% CI: 1.8-7.8; p<0.01) and a final diagnosis of renal disease (OR=3.4; 95% CI: 2.1-6.4; p<0.001) were factors that increased the odds of mortality in patients referring to the ED. Multivariate regression analysis in patients over 60 years showed that sepsis was an independent factor increasing the risk of death (OR=2.9; 95% CI: 1.3-5.9; p=0.009). A patient’s risk of death increases with an increase in the number of risk factors in that patient (r2=0.96; p=0.02). Conclusion: It appears the odds of mortality in patients referring to ED with cardiovascular complaints, a history of hypertensive, severe trauma, age over 60 and a final diagnosis of renal disease are higher versus other patients. In addition, the patients’ odds of death increase with an increase in the number of risk factors. Such an increase is more noticeable at age over 60.